Increasing English Vocabulary Skills Through The Singing Method At Elemantary Publich School Baruh 3 Sampang - Salim, Halimah (International Journal of Language and Ubiquitous Learning, 2023)
Background. Learning English is something that must be done at the time this modern. The learning process also plays an important role in acquisition of the language. Schools need additional language lessons English because of the lack of teaching hours from local teachers. Purpose. Children's needs in the school is something that must be completed because of learning English must be introduced from the elementary school level. Method. Learning English through songs can be an effective means qualified in improving the memory and ability of students in learning English, this can be proven by the ease with which songs are followed and remembered by the students.. Results. Presence of the English teachers at schools will greatly assist the early learning process from a foreign language, especially if the teacher can teach English in various ways. Conclusion. At the elementary level, such as elementary school, the emphasis on language learning should be emphasized English is at the most basic and most necessary language elements, namely: vocabulary, pronunciation, simple grammar, and simple conversation. Beside elements of the language, one thing that should always be remembered by English teachers is the importance of creating a comfortable and arousing situation and motivation to learn English.